Serum lipids and lipoproteins in children from families with early coronary heart disease - Özme, Şencan; Ege, Meltem; Özalp, İmran; Ciliv, Gönenç (The Turkish Journal of Pediatrics, 1977)
This study has been carried out to determine the plasma cholesterol and triglyceride levels of the children from families where one parent had had a myocardial infarction before age 45 (Group A), and to compare the results with those from the normal group (Group B). There were 43 children whose ages ranged from 6 to 17 years in the group A. Control group consisted of seventy five school children, aged 6 to 15 years, with no family history of myocardial infarction. The average cholesterol and triglyceride values were significantly higher than those of control group’s (p < 0.01). Almost half of the cases in the first group had pre beta band in the lipoprotein electrophoresis. Only 8.1 percent of the cases in the second group had the pre beta band. The difference was significant (p < 0.005).